2012
DOI: 10.1111/j.1875-595x.2011.00092.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy comparison of periapical infiltration injection of dexamethasone, morphine and placebo for postoperative endodontic pain

Abstract: Periapical infiltration of dexamethasone and morphine led to a considerable decrease in postoperative endodontic pain during the first 24 h after operation. Dexamethasone was more effective than morphine in pain reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 21 publications
2
27
0
3
Order By: Relevance
“…Dodson et al stated that using corticosteroids in dental procedures decreases pain significantly compared to other methods of pain relief (29). Shantiaee et al reported that using intracanal corticosteroids is among the most effective techniques to relieve endodontic pain (30). In our study, corticosteroids were the most commonly used intracanal medicaments for pain relief; this finding is in agreement with the results of previous studies (31).…”
Section: Discussionsupporting
confidence: 83%
“…Dodson et al stated that using corticosteroids in dental procedures decreases pain significantly compared to other methods of pain relief (29). Shantiaee et al reported that using intracanal corticosteroids is among the most effective techniques to relieve endodontic pain (30). In our study, corticosteroids were the most commonly used intracanal medicaments for pain relief; this finding is in agreement with the results of previous studies (31).…”
Section: Discussionsupporting
confidence: 83%
“…In this study, no adverse effects were detected which negates a previous study where dizziness was detected in 10% of patients after periapical infiltration injection of dexamethasone to control postoperative endodontic pain (Shantiaee et al 2012). Although some concerns may exist as to the harmful effects of the use of glucocorticoids, for example increasing the susceptibility to infection, a single dose has been reported to have no detrimental effects (Liesinger et al 1993, Alexander & Throndson 2000, Mehrvarzfar et al 2008.…”
Section: Discussionsupporting
confidence: 43%
“…Glucocorticoids are another class of drugs that prevent the production or release of inflammatory mediators. Previous studies have shown that dexamethasone can help reduce or prevent postoperative endodontic pain, regardless of the route of administration (single oral dose, periapical infiltration, or intraligamentary injection) 10,17,22) . Dexamethasone is well absorbed after oral administration and has a bioavailability of 61 to 86%.…”
Section: Introductionmentioning
confidence: 99%